User preference for HIV self-testing or self-sampling within a free online sexual health service: a service evaluation. (October 2019) - Baraitser, Paula; Black, Adam; Amos-Gibbs, Stuart; Holdsworth, Gillian; Ardines, Elena; Courtenay, Mollie; Howroyd, Chris; Brady, Michael
The objective of this study was to evaluate a service improvement project offering HIV testing through either self-testing or self-sampling in an online sexual health service by measuring type of test chosen and the reason for this choice. We created a web-page offering choice of online self-sampling or self-testing with information on the advantages and disadvantages of both methods. Anyone aged over 18 years resident in England, Scotland or Wales could order either type of test. We describe the characteristics of users, the tests chosen and the reasons for the choice. A total of 1502 HIV testing orders were placed and 1466 (97.6%) testing kits were dispatched after exclusion of multiple orders by the same user. Sixty-seven per cent of users chose self-testing (n = 984) and the rest chose self-sampling (n = 482, 32.9%). The most frequent reasons for choosing self-testing were: immediate results (n = 264, 46.9%), ability to complete the test themselves (n = 168, 29.8%), less blood required (n = 67, 11.9%) and the privacy of testing at home (n = 55, 9.8%). Public sector provision of self-testing as an adjunct to clinic-based HIV testing services is likely to be highly acceptable to UK populations. However, a proportion will prefer self-sampling, and maintaining choice of testing modality is important.